Innovation Strategy in Building an Organisational Culture that Supports Business Change: A Review from a Corporate Strategy Perspective - Ningsih, Susilowati; Tyas, Ari Anggarani Winadi Prasetyoning (Jurnal Penelitian Inovatif, 2024)
The era of globalization, technological advancement, and rapid market dynamics has created a highly volatile business environment. Companies are pressured to adapt to these changes or risk becoming obsolete and irrelevant. Innovation has become the key to addressing the challenges of business change. This research aims to investigate the relationship between innovation strategy, organizational culture, and corporate strategy in the context of business change, with the goal of providing better insights into how companies can build a culture that supports innovation as an integral part of their strategy. The research method employed in this study is a literature review using a qualitative approach and descriptive analysis. Descriptive analysis will be used to present and interpret findings from articles obtained from Google Scholar between 2011 and 2023. The study results indicate that in facing rapidly changing business dynamics, innovation is crucial to maintaining organizational relevance and competitiveness in a competitive market. Innovation strategy must be integrated into the organizational culture to create an environment where new ideas can flourish and be effectively implemented. Design-based approaches, supportive leadership, flexible organizational structures, and appropriate incentives are essential elements in building a strong culture of innovation.